2020
DOI: 10.1111/ejn.15078
|View full text |Cite
|
Sign up to set email alerts
|

Phonophobia and brainstem excitability in migraine

Abstract: Phonophobia in migraineurs may be due to lower hearing threshold (HT) and higher brainstem neuronal excitability. We report the correlation of phonophobia in migraineurs with HT, brain stem auditory evoked potential (BAEP) findings, and auditory triggers. Sixty-one migraineurs and 101 controls were included for HT, of whom 59 migraineurs and 31 controls had BAEP studies. Clinical details, migraine triggers, and headache frequency were noted. Hearing threshold was measured, and amplitudes of waves I to V of BAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Furthermore, in line with most of the studies quantifying auditory detection thresholds, we did not find differences between patients and controls or a correlation with phonophobia (1,2,5). Only one recent study did show clear differences in auditory detection thresholds between groups that did not correlate with the severity of phonophobia (34). We tentatively argue that it could have been affected by response biases using the MLI as especially lower thresholds were found in CM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in line with most of the studies quantifying auditory detection thresholds, we did not find differences between patients and controls or a correlation with phonophobia (1,2,5). Only one recent study did show clear differences in auditory detection thresholds between groups that did not correlate with the severity of phonophobia (34). We tentatively argue that it could have been affected by response biases using the MLI as especially lower thresholds were found in CM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Phonophobia might be an independent symptom of MD, which was found in 84% of MD patients and was unrelated to the presence of migraine [ 27 ]; this finding is inconsistent with the results of our study. Phonophobia might be attributed to lowered hearing threshold, which results from higher brainstem auditory neurol sensitivity [ 28 ]. This mechanism may explain our finding that phonophobia was infrequent in MD patients.…”
Section: Discussionmentioning
confidence: 99%
“…BAEP, a sensitive indicator of brainstem and auditory center injury, has wide applications in clinical diagnosis and treatment. BAEP will be altered when brain stem and auditory pathway are slightly injured, even if there are no clinical manifestations and signs [22][23][24] . In this study, it was found that the average bilirubin level in the BIND group was higher than that in the non-BIND group.…”
Section: Discussionmentioning
confidence: 99%